Ilmojen valloittaja - Verne, Jules, 1828-1905; Anttila, Werner, 1869-1954 (Salt Lake City, UT : Project Gutenberg, 2017)
"Ilmojen valloittaja" by Jules Verne is a novel written in the late 19th century. This story delves into themes of aviation and competition between different methods of flight, centering on the character Robur, who challenges the existing notions of air travel. The book is poised to explore both the scientific and societal implications of advances in flight technology. The opening of the novel introduces a scene filled with tension at a meeting of the Weldon Institute, spotlighting a heated debate among members regarding the feasibility of guided balloons versus heavier-than-air flying machines. Amid chaotic discussions, Robur, a formidable figure with exceptional physical and mental attributes, bursts onto the scene to assert that the future of aerial navigation rests not upon balloons but on flying machines with engines. His bold statements spark outrage among the balloon enthusiasts, leading to a dramatic confrontation as he stands his ground against overwhelming opposition. This introduction sets the stage for an exploration of conflicting ideas about aerial dominance and foreshadows the challenges Robur will face in his quest to advocate for innovation in flight. (This is an automatically generated summary.)
Release date is 2017-01-31
E-text prepared by Tapio Riikonen
Keywords: Science fiction; Aeronautics -- Fiction